177k views
3 votes
Please help me!!!!!!!!!!!!!​

Please help me!!!!!!!!!!!!!​-example-1
User Jaeo
by
5.9k points

1 Answer

5 votes

Answer: see proof below

Explanation:

Use the following Half-Angle Identities: tan (A/2) = (sinA)/(1 + cosA)

cot (A/2) = (sinA)/(1 - cosA)

Use the Pythagorean Identity: cos²A + sin²B = 1

Use Unit Circle to evaluate: cos 45° = sin 45° =
(\sqrt2)/(2)

Proof LHS → RHS

Given:
cot\ (22(1)/(2))^o-tan\ (22(1)/(2))^o

Rewrite Fraction:
cot\ ((45)/(2))^o-tan\ ((45)/(2))^o

Half-Angle Identity:
(sin(45)^o)/(1-cos(45)^o)-(sin(45)^o)/(1+cos(45)^o)

Substitute:
((\sqrt2)/(2))/(1-(\sqrt2)/(2))-((\sqrt2)/(2))/(1+(\sqrt2)/(2))

Simplify:
((\sqrt2)/(2))/((2-\sqrt2)/(2))-((\sqrt2)/(2))/((2+\sqrt2)/(2))


=(\sqrt2)/(2-\sqrt2)-(\sqrt2)/(2+\sqrt2)


=(\sqrt2)/(2-\sqrt2)\bigg((2+\sqrt2)/(2+\sqrt2)\bigg)-(\sqrt2)/(2+\sqrt2)\bigg((2-\sqrt2)/(2-\sqrt2)\bigg)


=(2\sqrt2+2)/(4-2)-(2\sqrt2-2)/(4-2)


=(4)/(2)

= 2

LHS = RHS: 2 = 2
\checkmark

Please help me!!!!!!!!!!!!!​-example-1
Please help me!!!!!!!!!!!!!​-example-2
User Svrist
by
6.0k points